Fundamental Research on a Unique Rotary Machine - Peng, Lixin (My University, 1994)
A unique rotary machine, which can be modified to function as an air motor, a hydraulic pump or a rotary combustion engine, has been developed. This thesis is concerned with both theoretical modelling of the engine aspects of the machine and the testing of a model and prototype. The machine is a simple rotational machine with an internal parallel axis arrangement. It is unique in the sense that there are two rotors turning in the same direction on their own stationary centres of gravity and working with the fluid around a full 360° degree path.
Using CAD/CAM techniques a model of the air motor and a prototype hydraulic pump were built and tested. Both of them have demonstrated very good performance features.
The engine described in this work is a true rotary engine with a unique semi-internal/external combustion system. It has a large power/weight ratio with a unique eight power strokes per revolution feature. Its multi fuel capability is a special contribution to the development of internal combustion engines where and when it is necessary to use alternative fuels.
A three zone turbulence eddy entrance thermodynamic model has been developed to predict the performance of the engine and optimize some of the structural and operational parameters. The results of the theoretical analysis indicate that this engine has excellent features which are improvements over those of the reciprocating engines as well as the Wankel rotary engine.
Keywords: Mechanical Engineering; Mechanical Engineering